Observation of Malaria Treatment with Dihydroartemisinin-Piperaquine Combination at Primary Health Care - Lambok Siahaan (Türkiye Parazitoloji Dergisi, 2022)

(untitled)
Objective:Dihydroartemisinin-Piperaquine (DHP) combination is the first-line treatment for uncomplicated malaria in Indonesia and has been used since 2010. This study was conducted to determine the efficacy of DHP combination for uncomplicated malaria treatment in a community-based evaluation.Methods:Recruitment was done by active or passive case detection. All uncomplicated malaria patients were treated with DHP once a day, for 3 days, administered orally (as is done in primary health care). Patients were followed up until day 28 post-treatment. The primary end point was a 28-day cure rate.Results:In this study, 484 subjects were screened through active and passive cases detection. A total of 45 subjects infected by P. vivax and 2 subjects infected by P. falciparum agreed to participate through written informed consent. There was no difference between clinical malaria and asymptomatic malaria in all analyzed characteristics. One patient had a D3 parasite density greater than 25% D0, although no parasites were found on the following day (D4). This study found 46 patients (97.9%) who had adequate clinical and parasitological responses. No adverse event was reported during the follow up of this study.Conclusion:DHP was effective, safe, and well tolerated in the treatment of uncomplicated malaria at primary health care.